The Analyze Of Investment For Alleviating Unemployment Problems in Banten Province - Sugeng Setyadi; Oki Oktaviana (Jambura Equilibrium Journal, 2021)
The amount of investment coming into the Banten province has not been in line with the absorption of labor so that the percentage of the unemployment rate in this region always shows above the national average. Therefore, this study aims to analyze the investment in the Banten region in order to obtain a strategy that can alleviate unemployment problems. The research was conducted through a qualitative descriptive approach carried out from August to November 2019. In addition to being based on secondary data obtained from legitimate institutions, to strengthen the results of the analysis, focus group discussions were carried out involving related stakeholders. The results showed that in terms of the distribution of investment in each district/ city, proportion of investment that comes from FDI and DDI or even government spending is dominated by the North Banten and Central Banten regions. So far, the sectors that have become the priority of investors are electricity, gas and water, transportation, warehousing, and telecommunications, which have relatively few workers. Increasing investment in the agribusiness sector is an alternative for efforts to accelerate the reduction in the unemployment rate in Banten Province. Various agribusiness sub-systems ranging from upstream, on-farm agribusiness, downstream agribusiness and agribusiness service provider sub-systems will absorb a lot of labor if realized Keywords: Unemployment; Investment; Qualitative Method